ln (x² - 2x) = 1
We know that ln b = log_e b where e is the "euler's number" (approx. 2.71828182845904523536...). If we convert the logarithm statement, we arrive at
e^1 = x² - 2x
Or...
x² - 2x - e = 0
By the quadratic formula,
x = [2 ± √(4 + 4e)]/2
We can take the sqrt 4 = 2
x = [2 ± 2√(e + 1)]/2
We can divide 2
x = 1 ± √(e + 1)
Thus, we have 2 solutions:
x = 1 + √(e + 1) or
x = 1 - √(e + 1)
Check...
ln(x² - 2x) = 1
ln [(1 + √(e + 1))² - 2(1 + √(e + 1))] = 1
ln (1 + 2√(e + 1) + e + 1 - 2 - 2√(e + 1)) = 1
ln e = 1
Thus,
1 = 1
For the other root...
ln [(1 - √(e + 1))² - 2(1 - √(e + 1))] = 1
ln (1 - 2√(e + 1) + e + 1 - 2 + 2√(e + 1)) = 1
ln e = 1
Thus,
1 = 1
^_^
2006-10-04 00:23:41
·
answer #1
·
answered by kevin! 5
·
0⤊
0⤋
to "eliminitate" ln you have to do e^ln :
you do it each side of the equation:
e^ [ ln(x^2-2x) ] = e^1
x^2 - 2x = e
x^2 - 2x - e = 0
using the quadratic formula, you find :
x = 1 - (e + 1)^½
x = 1 + (e +1)^½
Good luck !
2006-10-04 00:12:38
·
answer #2
·
answered by Vee A 1
·
0⤊
0⤋
ln(x^2-2x)=1
x^2-2x=e
x(x-2)-e=0
then just plug it into the quadratic equation
2006-10-04 00:05:47
·
answer #3
·
answered by quelforlor 2
·
0⤊
1⤋
x^2-2x=e
so
x= (2 +- sqrt(4-4(-e)) /2
= (2 +- sqrt(4+4e))/2
=(2+- 2sqrt(e))/2
x= 1+e^{1/2}
or
x= 1-e^{1/2}
2006-10-04 00:06:14
·
answer #4
·
answered by locuaz 7
·
0⤊
0⤋
Let's try this:
2006-10-04 00:05:09
·
answer #5
·
answered by ? 6
·
0⤊
1⤋